Outcomes of different transfer strategies for in vitro fertilization/intracytoplasmic sperm injection with poor-quality embryos−Analysis of embryonic development, perinatal period, and neonatal outcomes - Lei Jin; Zhou Li; Keyi Si; Bingxin Ma; Xinling Ren; Bo Huang (Heliyon, 2024)
During the in vitro fertilization and embryo transfer process, some expectant mothers may not have good embryos to choose from before the embryo transfer. Recommendations for this condition are currently unclear, and relevant clinical and neonatal outcomes are still lacking. This study analyzed the outcomes of poor-quality embryo transfers, including fetal outcomes, in the fresh cycle and frozen–thawed embryo transfer cycle. Embryos were also analyzed for abnormalities during the cleavage stage. The results indicate that in the absence of good embryos, clinicians and embryologists could advise expectant mothers to continue culturing the embryos to the blastocyst stage and undergo transfer if blastocysts are formed. This finding can also be used as a reference for many expectant mothers with frozen embryos that have not yet been thawed.